The effect of pharmaceutical companies' marketing mix strategies on physicians prescribing practices in Jordan: a cross-sectional study - Dana Hisham Al Thabbah; Mohammad Salameh Almahairah; Abdallah Y Naser; Hamzeh Mohammad Alrawashdeh; Mosaab Araidah (BMC, 2022)
Abstract Background Exploring the effect of different marketing mix strategies on physicians' prescribing practices is important due to its positive effect on the management of patients' diseases and improving the health status of individuals by promoting the use of the most cost-effective and safe treatment for patients. Aim This study aimed to assess the perceived influence of the four pharmaceutical marketing mix strategies (product, price, place, and promotion) on physicians' prescribing practices in Jordan. Method A quantitative survey study was conducted from May to November 2021 on practising physicians in Jordan. This research utilised a previously validated questionnaire developed by Hailu et al. The convenience sampling technique was used to recruit the study participants. The population of the study was practising physicians from the public and private sectors in Jordan. Any physician who was licensed to practice medicine in Jordan and actively engaged in patient care was considered eligible. The minimum sample size required was 379 participants, which was calculated based on a population size of 35,000 physicians in Jordan. Student t-test/One-way independent-measures ANOVA was used to compare the mean scores (indicating being affected by marketing mix elements between different demographic groups) after performing log transformation to restore the normality of the data. For the binary regression analyses, the dependent variable was the median score for each of the marketing mix elements. For each sub-scale and the overall scale, the median score was used to define the dummy variable used in the binary regression analysis. The study protocol was approved by the Scientific Research Ethics Committee at Isra University (SREC/21/06/005). Results A total of 315 physicians participated in the study. Overall, participating physicians showed moderate to high influence from marketing mix elements, with a median score of 141.0 (IQR: 118.0-156.0) out of 185, representing 76.2%. The lowest median score was found for the promotional tools used by pharmaceutical companies, with a median score of 48.5 (IQR: 40.0-56.0) out of 70, representing 69.3%. The highest median score found was for the pricing strategy implemented by pharmaceutical companies, with a median score of 25.0 (IQR: 18.8-28.0) out of 30, representing 83.3%. Working in private sector settings was an important predictor that increased the probability of physicians' prescribing practices being influenced by marketing mix elements (OR: 1.57; (95%CI: 1.00-2.47)), (p ≤ 0.05). Conclusion Physicians in our study were highly affected by marketing mix strategies, specifically price strategy. Policymakers should guarantee a balanced relationship with pharmaceutical companies and physicians. We should make sure that promotion strategies have a positive impact on patients' health. The government is advised to decrease the taxes on medications to decrease the overall cost for patients.